The effect of classical instrumental music (Kenny G–Style) on reducing anxiety in pregnant women during labor: A literature review - Rut Yohana Girsang; Dilma’aarij Agustia; Novitri Adelina Sipayung; Dinda Dian Meidita; Ria Fazelita Gultom (Science Midwifery, 2026)
Maternal anxiety during labor remains a significant psychological condition that may adversely affect labor progression, pain perception, and overall childbirth outcomes. Non-pharmacological interventions, particularly music therapy, have been increasingly recognized as complementary strategies to improve maternal psychological well-being. This literature review aims to examine the effectiveness of classical and instrumental music, including the style of Kenny G, in reducing anxiety among pregnant women during labor. A systematic literature review was conducted by searching peer-reviewed articles published between 2018 and 2025 in databases including PubMed, Scopus, ScienceDirect, and Google Scholar. Keywords used included “music therapy,” “labor anxiety,” “pregnancy,” “childbirth,” and “relaxation music.” The findings indicate that exposure to calming instrumental music is associated with reduced anxiety levels, decreased physiological stress markers (such as heart rate and cortisol), and improved maternal relaxation during labor. The slow tempo and smooth melodic structure characteristic of instrumental jazz and contemporary classical music, including Kenny G’s compositions, are associated with activation of the parasympathetic nervous system, promoting relaxation and emotional stability. Overall, music therapy is a safe, low-cost, and non-invasive intervention that can be integrated into midwifery care to enhance maternal comfort during childbirth.